Epidemiology of peripheral nerve injuries in sports, exercise, and recreation in the United States, 2009 - 2018 - Li, N. Y.; Onor, G. I.; Lemme, N. J.; Gil, J. A. (The Physician and Sportsmedicine, 2021)
Objective To assess rates of peripheral nerve injuries (PNI) in sport, exercise, and recreational activities.